Determining a Better Metric for RFID Performance in Environments with varying Noise Levels - Mallinson, Hugo; Hodges, Steve; Thorne, Alan (12th IEEE International Conference on Methods and Models in Automation and Robotics, 2006)
Often users wish to maximize the range of a passive RFID system. At the furthest extent of their range the signal between tag and reader will be at the weakest level which the reader can detect. It is desirable to know how close a system is to operating at this level, since the data being transmitted will be increasingly susceptible to small increases in the channel noise. This paper examines two techniques to survey an RFID system’s performance, and investigates two sampled environments: a large bare room, and a manufacturing facility with extensive fixturing. It seeks to 1) identify a useful metric for measuring the performance of an RFID tag and reader in a given configuration and 2) evaluate methods for surveying this performance across a space to be used for an RFID system deployment.